Peran Tata Kelola Perusahaan dan Ungkitan dalam Memengaruhi Financial Distress pada Perusahaan Non-Cylicals di Indonesia - Artwidi Fitrianingrum; Shinta Permata Sari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study examines the impact of corporate governance and leverage on financial distress in non-cyclicals sector companies listed on the Indonesia Stock Exchange in 2021 to 2023. Using a quantitative approach, multiple linear regression analysis is applied to assess the influence of institutional ownership, managerial ownership, the board of directors, the board of commissioners, independent commissioners, the audit committee, and leverage on financial distress that measured by the Altman Z-score model. The sample selected using purposive sampling based on specific criteria. The findings reveal that the board of directors, independent commissioners and leverage affect financial distress, underscoring their pivotal roles in corporate financial stability. The board of directors' strategic financial decisions directly influence a firm's fiscal health, while high leverage exacerbates financial distress due to excessive debt burdens. Conversely, institusional ownership, managerial ownership, the board of commissioners and the audit committee do not affect financial distress, likely due to their advisory and oversight roles rather than direct involvement in financial management. These findings contribute to the discourse on corporate governance and financial distress, offering insights for policymakers, investors, and corporate leaders.